2019
DOI: 10.1155/2019/5893028
|View full text |Cite
|
Sign up to set email alerts
|

“Gut Microbiota-Circadian Clock Axis” in Deciphering the Mechanism Linking Early-Life Nutritional Environment and Abnormal Glucose Metabolism

Abstract: The prevalence of diabetes mellitus (DM) has been increasing dramatically worldwide, but the pathogenesis is still unknown. A growing amount of evidence suggests that an abnormal developmental environment in early life increases the risk of developing metabolic diseases in adult life, which is referred to as the “metabolic memory” and the Developmental Origins of Health and Disease (DOHaD) hypothesis. The mechanism of “metabolic memory” has become a hot topic in the field of DM worldwide and could be a key to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…The composition of the gut microbiota is subject to diurnal variation and is entrained by host circadian rhythms. In turn, a diverse microbiota is essential for optimal regulation of host circadian pathways [68,72,73]. Additionally, significant relationships between nutrient intake and the circadian clock have been shown.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the gut microbiota is subject to diurnal variation and is entrained by host circadian rhythms. In turn, a diverse microbiota is essential for optimal regulation of host circadian pathways [68,72,73]. Additionally, significant relationships between nutrient intake and the circadian clock have been shown.…”
Section: Reviewsmentioning
confidence: 99%
“…Additionally, significant relationships between nutrient intake and the circadian clock have been shown. Considering whether dysbiosis associated with sleep and circadian misalignment in shift workers affects clock genes in metabolic tissues will be important in future studies [68]. Only one narrative review searched for a link between exposure to occupational agents, changes in the microbiome, and possible development of health complications, in particular autoimmune disorders.…”
Section: Reviewsmentioning
confidence: 99%
“…What is the critical mechanism mediating the “metabolic memory”? Although emerging studies began to pay attention to the potential role of central hypothalamic regulation, [ 45 ] gut microbiota, [ 46 , 47 ] circadian rhythm, [ 48 , 49 ] and brown adipose tissue [ 50 , 51 ] in linking the early-life nutrition and metabolic health in later life, we mainly overviewed the evidence regarding the epigenetic regulation in this review. Sib-pairs study, one exposure to diabetes and the other to a non-diabetes in utero, indicated that metabolic programming was independent of genetic inheritance to some content.…”
Section: Role Of Epigenetics In Mediating the Metabolic Programmingmentioning
confidence: 99%
“…Individuals come into close contact with microorganisms, particularly the intestinal microbes that affects the development and maintenance of the immune system, after childbirth (may before; Gensollen et al, 2016; Mishra et al, 2021). The decreased diversity of the microbiota residing in the intestine, the largest human immune organ (Pan et al, 2020; Zhou et al, 2019), has been found in a variety of infectious diseases (Geng et al, 2020; Haak et al, 2018; Lv et al, 2019). These suggest that the impaired homeostasis of the intestinal microbiota may promote the development of infectious diseases, and the balance of intestinal microecology is essential for the prevention and control of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…. The decreased diversity of the microbiota residing in the intestine, the largest human immune organ (Pan et al, 2020;Zhou et al, 2019), has been found in a variety of infectious diseases (Geng et al, 2020;Haak et al, 2018;Lv et al, 2019). These suggest that the impaired homeostasis of the intestinal microbiota may promote the development of infectious diseases, and the balance of intestinal microecology is essential for the prevention and control of infectious diseases.…”
mentioning
confidence: 99%